2021
DOI: 10.18632/aging.203418
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of abnormal angiotensin-converting enzyme 2 expression correlated with immune infiltration after SARS-CoV-2 infection in the prognosis of breast cancer

Abstract: The potential role of abnormal ACE2 expression after SARS-CoV-2 infection in the prognosis of breast cancer is still ambiguous. In this study, we analyzed ACE2 changes in breast cancer and studied the correlation between ACE2 and the prognosis and further analyzed the relationship between immune infiltration and the prognosis of different breast cancer subtypes. Finally, we inferred the prognosis of breast cancer patients after SARS-CoV-2 infection. We found that ACE2 expression decreased significantly in brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(26 reference statements)
0
5
1
Order By: Relevance
“…Nevertheless, in patients receiving chemotherapy, elevated ACE2 was correlated with worse RFS and DMFS compared with patients with low ACE2 expression. This finding is inconsistent with the result reported in a recent publication showing that elevated ACE2 immunostaining is unrelated to the outcome in nonspecific types of invasive breast cancer [ 49 ]. This inconsistency may be due to the fact that the aforementioned study only focused on the expression level of ACE2, but did not include the treatment modality of the patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in patients receiving chemotherapy, elevated ACE2 was correlated with worse RFS and DMFS compared with patients with low ACE2 expression. This finding is inconsistent with the result reported in a recent publication showing that elevated ACE2 immunostaining is unrelated to the outcome in nonspecific types of invasive breast cancer [ 49 ]. This inconsistency may be due to the fact that the aforementioned study only focused on the expression level of ACE2, but did not include the treatment modality of the patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings also imply that upregulation of ACE2 in cancer tissues with originally low ACE2 expression may be a driver of cancer progression. This possibility is partly supported by a recent study showing that higher ACE2 expression appears to be associated with higher histological grade, HER2-enriched and Basal-like subtypes [ 49 ]. These indicators are known to be associated with poor prognosis in breast cancer.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Jiang et al. suggested that breast tumor tissues can be further reduced at ACE2 expression level (angiotensin-converting enzyme 2) after SARS-CoV-2 infection, which further deteriorates immune infiltration and worsens the prognosis of luminal B breast cancer after SARS-CoV-2 infection ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cluster 2: Recovery of breast cancer patients in the pandemic A paper suggested that the treatment of ACEIs (angiotensinconverting enzyme ACE inhibitors) in Luminal A breast cancer might facilitate tumor progression (44). Jiang et al suggested that breast tumor tissues can be further reduced at ACE2 expression level (angiotensin-converting enzyme 2) after SARS-CoV-2 infection, which further deteriorates immune infiltration and worsens the prognosis of luminal B breast cancer after SARS-CoV-2 infection (45).…”
Section: Cluster 1: Breast Cancer Surgery In the Pandemicmentioning
confidence: 99%